2020
DOI: 10.3390/ani10101754
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Pork from Entire Male and Immunocastrated Pigs for Meat Products—An Overview with Recommendations

Abstract: Due to the strong public initiative in Europe and increased regulator focus to mitigate pain, surgical castration of pigs is being gradually abandoned, while the importance of other sex categories like entire males (EM) and immunocastrates (IC) increases. Although beneficial for animal welfare and economics, their use also brings forward several quality problems. Besides the occurrence of boar taint in EM, these include excessive carcass leanness, softer fat, meat color and pH deviations, inferior water holdin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 147 publications
(282 reference statements)
1
29
0
Order By: Relevance
“…Significant differences ( p < 0.05) between different sire lines in pH 45 were observed (i.e., the highest values in C and the lowest in B); however, no differences could be found between different male categories for this trait. In agreement with the results of this study, the results of the three meta-analyses showed no or very small difference between different male categories in the case of muscle pH, indicating this trait to be without actual practical importance in regard to sex categories [ 7 , 26 , 32 , 65 ]. We also found a significant interaction ( p < 0.001) between the TSL*MC on initial pH values ( Figure 2 A; Table S1 ).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Significant differences ( p < 0.05) between different sire lines in pH 45 were observed (i.e., the highest values in C and the lowest in B); however, no differences could be found between different male categories for this trait. In agreement with the results of this study, the results of the three meta-analyses showed no or very small difference between different male categories in the case of muscle pH, indicating this trait to be without actual practical importance in regard to sex categories [ 7 , 26 , 32 , 65 ]. We also found a significant interaction ( p < 0.001) between the TSL*MC on initial pH values ( Figure 2 A; Table S1 ).…”
Section: Resultssupporting
confidence: 90%
“…Similar to the result for animals originating from TSL B, in the investigation of Škrlep et al (2011) [ 43 ] on two types of crossbreds (Duroc and Pietrain sired), drip loss measured after 24 h and 48 h was also influenced by sex and crossbreed type interaction but without any differences between the MCs. The results of individual studies investigating only the sex type as an influential factor are ambiguous; however, generally, no difference between different sex types was found for this trait [ 7 , 32 , 49 ]. It should be noticed that observed drip loss was quite high in all investigated groups; however, this may be more related to the relatively low age of the animals, especially for entire males, which still did not manage to exhibit their full physiological potential at this stage of growth and development [ 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various approaches have been investigated to control boar taint-related compounds [ 19 ], with gene-editing showing huge potential, but also a rather lengthy timeline before commercial implementation. While some approaches may address decreasing the incidences of boar taint, they do not necessarily address the welfare issues of entire male production, such as aggressive behavior [ 20 ], the meat/product quality issues associated with entire males [ 21 ], or the application of these technologies, such as gene editing, is currently limited in various countries. Thus, commercial interest in the use of immunocastration has increased, which entails vaccinating the animal against its own gonadotropin-releasing hormone (GnRH).…”
Section: Introductionmentioning
confidence: 99%